Composite Materials: Fatigue and Fracture (Third Volume) 1991
DOI: 10.1520/stp17717s
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Mode Fracture in Fiber-Polymer Composite Laminates

Abstract: Mode I, Mode II, and Mixed-Mode I/II interlaminar tests on unidirectional carbon-fiber composites have been conducted using beam specimens. Both a thermosetting-based (an epoxy resin) matrix and a thermoplastic-based (poly(ether-ether ketone)) matrix have been employed. The fracture energy, Gc, has been ascertained and the various correction factors that need to be applied if accurate results are to be obtained are described. Where Mixed-Mode I/II loadings may have been present, the measured value of Gc has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…As shown in criterion based on a critical Mode I or Mode II crack opening displacement [28] (COD) also failed to produce a response similar to those exhibited by the materials presented herein.…”
Section: New Bilinear Criterionmentioning
confidence: 52%
“…As shown in criterion based on a critical Mode I or Mode II crack opening displacement [28] (COD) also failed to produce a response similar to those exhibited by the materials presented herein.…”
Section: New Bilinear Criterionmentioning
confidence: 52%
“…Wang et al 26 observed that the critical energy release rate for mixed mode loading increases with an increasing mode II loading component. Failure loci have been established by Hashemi et al 5,27 based on a critical crack opening displacement or with an interaction parameter, I i , which varies linearly between 0 and 1 and is a function of the ratio…”
Section: Mixed Mode Failure Criteriamentioning
confidence: 99%
“…Fracture surfaces from coupons tested under different known modes of loading were examined. These known modes of loading were obtained by testing standard fracture mechanics specimens (Double Cantilever Beam (DCB) for mode I tests 1,2 , End Loaded Split (ELS) for mode II tests 3,4,5 , Fixed Ratio Mixed Mode (FRMM) for mixed mode ratio I:II=4:3 tests 3,4,5 and Mixed Mode Bending (MMB) which can be used for any mixed mode loading ratio 6 ) under both static and fatigue loading. The material examined was a carbon fibre/epoxy composite that is manufactured by Ciba Composites (T300/914).…”
Section: Introductionmentioning
confidence: 99%
“…The authors' partition theory based on classical beam theory [6][7][8][9][10] has given excellent predictions of mixed-mode fracture toughness for delamination in generally laminated composite beams [8][9][10] when compared against the experimental test data from some independent comprehensive testing [11][12][13][14][15][16][17][18][19][20]. In comparison, mixed-mode partition theories based on 2D elasticity [1,4] have shown poor correlation with experimental results.…”
Section: Introductionmentioning
confidence: 99%